EFEKTIVITAS PELAKSANAAN MODEL PELATIHAN BLENDED LEARNING PADA PELATIHAN KEPEMIMPINAN APARATUR SIPIL NEGARA: (Studi Pada Penyelenggaraan Pelatihan Kepemimpinan di Lembaga Administrasi Negara Republik Indonesia) - Heronika Wahyu Maninggar (Jurnal Administrasi Publik, 2023)
This research aims to evaluate the effectiveness of implementing the blended learning method in leadership training at the National Institute of Public Administration (LAN). This method combines online learning and face-to-face interaction and has been implemented in national leadership training at LAN. However, there has been no evaluation conducted to assess the effectiveness of this method. This research uses the Goal-Approach framework developed by Bowyer and Chambers (2017) to evaluate the effectiveness of blended learning implementation. The evaluation is conducted through three outcome indicators: participant satisfaction, participant engagement, and learning outcomes. The analysis results show that participants provide positive assessments of the training organization, the learning process, and the usefulness of the learning for future purposes. Participants also express satisfaction with the environment, facilities, and learning processes. Despite facing communication challenges in the distance learning method, participants remain engaged in blended learning. The learning outcomes demonstrate good effectiveness, with high pass rates and participant scores. Overall, this research indicates that the blended learning method is effective in leadership training at the National Institute of Public Administration (LAN).